2022
DOI: 10.3390/life13010119
|View full text |Cite
|
Sign up to set email alerts
|

A Voxel-Based Morphometric Study of Gray Matter in Specific Phobia

Abstract: The objective of this study was to analyze the neurostructural abnormalities of brain areas responsible for the acquisition and maintenance of fear in small animal phobia by comparing gray matter volume (GMV) in individuals with phobia and non-fearful controls. Structural magnetic resonance imaging was obtained from 62 adults (79% female) assigned to one of two groups: 31 were diagnosed with small animal phobia and 31 were non-fearful controls. To investigate structural alterations, a whole-brain voxel-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…When the phobia subgroups were combined and compared to the control group, a significant volume increase was observed in the right OFC (Hilbert et al, 2015). Last but not least, a more recent study compared SAP individuals and healthy controls and found smaller GMV (gray matter volume) (in SAP individuals in the right and left insula, in the orbitofrontal cortex, in the left superior medial frontal, right superior frontal, and right anterior cingulate cortex (Rivero et al, 2023). SAP individuals also displayed larger GMV in the left putamen.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…When the phobia subgroups were combined and compared to the control group, a significant volume increase was observed in the right OFC (Hilbert et al, 2015). Last but not least, a more recent study compared SAP individuals and healthy controls and found smaller GMV (gray matter volume) (in SAP individuals in the right and left insula, in the orbitofrontal cortex, in the left superior medial frontal, right superior frontal, and right anterior cingulate cortex (Rivero et al, 2023). SAP individuals also displayed larger GMV in the left putamen.…”
Section: Introductionmentioning
confidence: 97%
“…To our knowledge, this marks the first attempt of applying such a technique in this context. We hypothesize that specific brain structures, previously identified in separate studies as crucial in emotional regulation and the fear response mechanismsuch as the orbitofrontal cortex, amygdala, and basal gangliacan effectively differentiate these two groups (Mourao-Miranda et al, 2012;Rivero et al, 2023;Rondina et al, 2018;Vai et al, 2020). By employing BSVM, we can precisely quantify the contribution of each brain region to our classification models, identifying the most critical areas, assigning a weight to each, and highlighting the neurobiological distinctions between SAP individuals and CTRL ones (control individuals).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation